JOB SATISFACTION: A BIBLIOMETRIC ANALYSIS - Prilatama, Aris; Churiyah, Madziatul (Transpublika Publisher, 2023)
This study aims to conduct a bibliometric analysis of co-authorship, co-occurrence, and citation related to job satisfaction. The method used in this study involves selecting the keyword